“Malaysia’s policy towards the Rohingya refugees = Polisi Malaysia terhadap pelarian Rohingya - Muzafarkamal, Nur Syazwani; Hossain, Ishtiaq (IIUM Press, 2019)
This paper focuses on Malaysia’s policy towards the Rohingya refugees in the country. It is divided into four parts. The first part of this Chapter analyses the reasons for the Rohingyas to choose to come to Malaysia. The next part discusses the Immigration Act 1967 as part and parcel of any adopted policy. Interviews and related documents have been used to guide this research in order to achieve this objective. Finally, the last part explains the perceptions of government agencies, as well as the NGOs towards the arrival of the Rohingya to Malaysia. In addition, the role of the UNHCR in Malaysia will be elaborated.